Improving Students™ Speaking Skill Achievement Through Tiktok Application Video - Martuah Saragih, Juni Ari; Amin, Teguh Satria (Universitas Negeri Medan, 2024)
This research aimed to improved the students™ speaking skill in English lesson by using action learning strategy. This research was conducted by using Classroom Action Research (CAR). The subject of this research was VIII-A grade of SMPS Plus Kasih Ibu Patumbak which consisted of 20 students. The objective of this research was to Improving Students™ Speaking Skill Achievement Through Tiktok Application Video. This research was conducted in two cycles which each consists™ of planning, acting, observing, and reflecting. The data were gathered through quantitative. The result showed the increasing of students score from the pre-test to post-test II. In pre-test, there was only 10 % (2 stadents) who get point . In post-test 1, there was only 35% (7 studens) who get point , 10 post-test II, there was 90 % (18 students) who get point . Besides that, TikTok Application video helped the students to created the creative class.